IMPACT OF LEVOSIMENDAN ON RENAL FUNCTION IN COMPLEX TREATMENT OF ACUTE DECOMPENSATED HEART FAILURE - M. V. Lediakhova; S. N. Nasonova; I. V. Zhirov; M. V. Andreevskaya; R. M. Bogieva; T. M. Uskach; M. A. Saidova; V. P. Masenko; S. N. Tereshchenko (Столичная издательская компания, 2018)
Background. Levosimendan infusion can be used in the treatment of patients with acute decompensated heart failure (ADHF) with a reduction in cardiac output and signs of severe congestion/pulmonary edema.Aim. To study impact of levosimendan on renal function in patients with ADHF with reduced systolic function.Material and methods. The study was a prospective, randomized trial. We enrolled 30 men (age 62.5 [55.8-69.3] years) hospitalized with ADHF with reduced systolic function (left ventricular ejection fraction <40%), increased level of brain natriuretic peptide (BNP>500 pg/mL) and systolic blood pressure >125 mmHg. All patients were randomized into 2 groups of 15 people each. In the first group, the patients received an intravenous infusion of levosimendan 0.1 μg/kg/min for 24 hour added to standard therapy. The second group received standard therapy.Results. 24-hour levosimendan infusion significantly increased the glomerular filtration rate levels from 65.4 [45.2-99.2] mL/min/1.73m2 at baseline to 79.0 [66.3-93.1] mL/min/1.73m2 at discharge (p= 0.011), greatly decreased serum creatinine from 1.17 [0.90-1.55] mg/dL at baseline to 1.01 [0.89-1.14] mg/dL at discharge (p = 0.009) and blood urea nitrogen and at the same time improved renal blood flow in patients with ADHF while there were no clinically significant changes in the studied parameters in the standard therapy group.Conclusion. Levosimendan had a positive effect on renal function in patients with ADHF with reduced systolic function.